Increased Anxiety and Depression Among Belgian Sexual Minority Groups During the First COVID-19 Lockdown—Results From an Online Survey - Reyniers, Thijs; Buffel, Veerle; Thunnissen, Estrelle; Vuylsteke, Bea; Siegel, Magdalena; Nöstlinger, Christiana; Wouters, Edwin (Frontiers in Public Health, 2022)
The COVID-19 pandemic most likely had a negative impact on mental health. Sexual minorities are at higher risk for adverse mental outcomes such as depression, anxiety, suicidal ideation. Such mental health disparities may have exacerbated during the COVID-19 pandemic, due restricted real-life social contact. The purpose of this study was to examine changes in depression, anxiety, and suicidal ideation among Belgian sexual minority adults between the periods before and during the first COVID-19 lockdown. We conducted an online survey, which was disseminated by community organizations throughout Belgium in April 2020. The questionnaire included two-item Generalized-Anxiety-Disorder (GAD-2) and Patient-Health-Questionnaire (PHQ-2) measures. We included 965 fully completed questionnaires in the analysis. During the lockdown, the proportions of participants screening positive for depression and anxiety increased from 13.5% to 29.3% (p<0.001), and from 25.7% to 37.1% (p<0.001) respectively. Lonely and young participants were more likely to acquire depression. About 20% had suicidal thoughts during the lockdown. Our findings indicate that the COVID-19 pandemic has exacerbated already existing mental health disparities between sexual minority adults and the general population. These exacerbations may be the result of increased loneliness and social isolation. The results highlight the need for stimulating and strengthening social connectedness within the LGBTQI community during and in the aftermath of the COVID-19 pandemic, and the need of maintaining mental health services for such groups during pandemic restrictions.